Experiences and challenges in the health protection of medical teams in the Chinese Ebola treatment center, Liberia: a qualitative study - Ying Li; Huan Wang; Xu-Rui Jin; Xiang Li; Michelle Pender; Cai-Ping Song; Sheng-Lan Tang; Jia Cao; Hao Wu; Yun-Gui Wang (BMC, 2018)
Abstract Background Health care workers are at the frontline in the fight against infectious disease, and as a result are at a high risk of infection. During the 2014-2015 Ebola outbreak in West Africa, many health care workers contracted Ebola, some fatally. However, no members of the Chinese Anti-Ebola medical team, deployed to provide vital medical care in Liberia were infected. This study aims to understand how this zero infection rate was achieved. Methods Data was collected through 15 in-depth interviews with participants from the People's Liberation Army of China medical team which operated the Chinese Ebola Treatment Center from October 2014 to January 2015 in Liberia. Data were analysed using systematic framework analysis. Results This study found numerous bio-psycho-socio-behavioural risk factors that directly or indirectly threatened the health of the medical team working in the Chinese Ebola Treatment Center. These factors included social and emotional stress caused by: (1) the disruption of family and social networks; (2) adapting to a different culture; (3) and anxiety over social and political unrest in Liberia. Exposure to Ebola from patients and local co-workers, and the incorrect use of personal protective equipment due to fatigue was another major risk factor. Other risk factors identified were: (1) shortage of supplies; (2) lack of trained health personnel; (3) exposure to contaminated food and water; (4) and long working hours. Comprehensive efforts were taken throughout the mission to mitigate these factors. Every measure was taken to prevent the medical team's exposure to the Ebola virus, and to provide the medical team with safe, comfortable working and living environments. There were many challenges in maintaining the health safety of the team, such as the limited capability of the emergency command system (the standardized approach to the command, control, and coordination of an emergency response), and the lack of comprehensive international protocols for dealing with emerging infectious disease pandemics. Conclusions The comprehensive and multidisciplinary measures employed to protect the health of the medical team proved successful even in Liberia's resource-limited setting. The global health community can learn valuable lessons from this experience which could improve the safety of health care workers in future emergencies. These lessons include: establishing capable command systems; implementing effective coordination mechanisms; providing adequate equipment; providing training for medical teams; investing in the development of global health professionals; and improving research on ways to protect health care workers.